The avalanche handbook - McClung, David; Schaerer, P. A. (Peter A.) (Mountaineers Books, 2022)
"An updated edition of the classic instructional guide, this fourth edition of The Avalanche Handbook includes detailed information on the basics of avalanches; trends in avalanche safety; effects of mountain snow climates and weather on avalanches; snow and avalanche formation and growth; avalanche terrain, motion, and effects; elements of applied avalanche forecasting; factors to consider in evaluating and forecasting avalanches; risk management and risk reduction strategies; safety measures and rescue techniques; and avalanche protection, including avalanche detection and control."--